Characterization of carbapenem-resistant Klebsiella pneumoniae in bloodstream infections: antibiotic resistance, virulence, and treatment strategies - Zhong, Chenglin; Lin, Shaohua; Li, Zeqi; Yang, Xuejing (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCarbapenem-resistant Klebsiella pneumoniae (CRKP) infections pose a major clinical challenge due to multidrug resistance. This study evaluated the clinical features, antibiotic resistance mechanisms, virulence factors, and the potential therapeutic impact of berberine hydrochloride (a traditional Chinese medicine) in CRKP infections.MethodsNinety-four CRKP isolates from bloodstream infections at the First Affiliated Hospital of Zhejiang Chinese Medical University were characterized for carbapenemase genes, antibiotic susceptibility, and virulence determinants. Clinical data were analyzed to identify risk factors for CRKP infection, and the in vitro antibacterial activity of berberine hydrochloride was assessed.ResultsMost of the isolates (71.3%) were from the intensive care unit (ICU) patients. The blaKPC gene was the predominant resistance mechanism (62.77%), while the virulence genes uge (93.62%) and wabG (92.55%) were highly prevalent. ICU admission, male sex, respiratory diseases, invasive procedures, prior use of third-generation cephalosporinase inhibitors, and absence of traditional Chinese medicine treatment were linked to poorer outcomes. Importantly, berberine hydrochloride inhibited CRKP growth in vitro, with a minimum inhibitory concentration (MIC) of 125 mg/mL.ConclusionOur study reveals the multifaceted resistance and virulence profiles of CRKP in bloodstream infections and highlights the potential clinical value of berberine hydrochloride as an adjunctive therapeutic agent. These findings support further clinical investigations into incorporating traditional Chinese medicine to improve outcomes in patients with CRKP bloodstream infections.